Trends in the Formation of Disability Due to Multiple sclerosis in Moscow in 2014-2021 - S. P. Zapariy; A. G. Samusenko; Yu. E. Vyazovichenko; A. V. Svetlichnaya; A. N. Gerasimov; N. V. Torchinsky (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. Multiple sclerosis (MS) is a chronic progressive neurodegenerative autoimmune disease of the central nervous system, affecting mainly people of working age and leading to disability. Since this disease is a frequent cause of persistent disability, the importance and at the same time insufficiency of research in the field of regional specific programs related to disability due to MS is noted. Aims. To study the dynamics and features of the formation of primary and repeated disability due to MS among various age groups of the population, taking into account gender characteristics and severity of disability in Moscow in 2014–2021. Materials and methods. The study used examination materials of persons over 18 years of age with MS, collected in an electronic database of medical and social expertise (ITU) of the Federal State Institution "ITU Main Bureau for Moscow", acts, protocols of ITU, static f-088/06 on the re-examination of RS. Results. The last 8 years have been characterized by a decrease in general disability due to MS, with a decrease in the number of persons recognized as disabled for the first time (VPI) and an increase in the number of persons re-recognized as disabled (PPI). There is a drop in the proportion of disabled people of the first and second disability groups with an increase in the third group. In the structure of VPI and PPI due to MS, persons of working age prevailed with a slight decrease in the group of PPI. The gender structure was dominated by female persons. Conclusion. The study of indicators of disability due to MS among various population groups in modern conditions is of great importance for monitoring the level of disability of patients and maintaining a socially active life of the patient.